2020
DOI: 10.1097/md.0000000000019981
|View full text |Cite
|
Sign up to set email alerts
|

Universal antibiotic prophylaxis may no longer be necessary for patients with acute variceal bleeding

Abstract: A few decades ago, antibiotic prophylaxis for patients with acute variceal bleeding was reported beneficial. However, endoscopic and systemic therapy for variceal bleeding has dramatically improved since then, so the necessity of prophylactic antibiotics can be questioned. In this study, we reevaluated the efficacy of antibiotic prophylaxis in acute variceal bleeding, using the most recent data in our hospital. We retrospectively analyzed the medical records of 150 patients with acute variceal blee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…To reexamine the efficacy of antibiotic prophylaxis in cirrhotic patients, we performed a retrospective study and found that antibiotic prophylaxis was not significantly associated with lower rates of bacterial infection, rebleeding, readmission, or mortality. 6 Despite the low rate of antibiotics prescribing (30.7%), the frequency of bacterial infection (3.3%) was much lower than in previous reports. 6 In their study, Zullo et al did not mention anything about the association between antibiotic prophylaxis and clinical outcomes; however, sepsis occurred in only 2.4% of their patients, less than half of which resulted in mortality.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…To reexamine the efficacy of antibiotic prophylaxis in cirrhotic patients, we performed a retrospective study and found that antibiotic prophylaxis was not significantly associated with lower rates of bacterial infection, rebleeding, readmission, or mortality. 6 Despite the low rate of antibiotics prescribing (30.7%), the frequency of bacterial infection (3.3%) was much lower than in previous reports. 6 In their study, Zullo et al did not mention anything about the association between antibiotic prophylaxis and clinical outcomes; however, sepsis occurred in only 2.4% of their patients, less than half of which resulted in mortality.…”
mentioning
confidence: 67%
“…6 Despite the low rate of antibiotics prescribing (30.7%), the frequency of bacterial infection (3.3%) was much lower than in previous reports. 6 In their study, Zullo et al did not mention anything about the association between antibiotic prophylaxis and clinical outcomes; however, sepsis occurred in only 2.4% of their patients, less than half of which resulted in mortality. 1 We present here a summary of the results of all randomized controlled trials that were included in the systematic review 2 ; randomized controlled trials reported after that 7,8 ; the present study by Zullo et al 1 ; and our updated data 9 (Table 1).…”
mentioning
confidence: 67%
“…A total of 15 studies (1933 subjects) reported outcome data on mortality risk among cirrhosis patients with UGIB. 8,9,13,14,16,[18][19][20][21][22]30,32,[34][35][36][37] The pooled risk of 6week mortality (CTP-A: 0%, CTP-B: 4.7%, CTP-C: 20.0%) increased proportionally with the underlying CTP class. Antibiotic prophylaxis reduces the risk of 6week mortality (RR = 0.72, 95% CI = 0.57-0.90, I 2 = 0%) (Figure 1).…”
Section: Mortalitymentioning
confidence: 99%
“…A total of 9 studies (2235 subjects) reported outcome data on the risk of rebleeding among cirrhosis patients with UGIB. 8,13,14,16,21,[30][31][32]35,36 Antibiotic prophylaxis was associated with a significantly lower pooled risk of rebleeding within 7 days (RR = 0.45, 95% CI = 0.29-0.72, I 2 = 47%) (Figure 4A) and 6 weeks (RR = 0.57, 95% CI = 0.46-0.71, I 2 = 61%) (Figure 4B). The heterogeneity for rebleeding at 6 weeks was resolved when analysis was restricted to RCTs (RR = 0.59, 95% CI = 0.44-0.79, I 2 = 0%) (Supporting Information: Table 2).…”
Section: Bleeding-related Complicationsmentioning
confidence: 99%
See 1 more Smart Citation